Marx's social ontology : individuality and community in Marx's theory of social reality - Gould, Carol C. (Cambridge [Massachusetts] : MIT Press, 1980)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Marx, Karl; communistische ideologie